An in vivo feasibility study investigating the fixation of osteotomised rabbit tibia using a bioresorbable composite plate and a comparison of the effects of the bioresorbable plate and a metal plate on intact bone - Qureshi, Assad (2018)
Background: Modern fracture management uses surgically implanted metal plates to fix fractured bones to restore pre-injury anatomy. Following healing, the plate may have to be removed requiring a second operation. Reactive thinning of the bone beneath the metal plate (stress shielding) can increase the theoretical risk of re-fracture once the plate is removed. Bioresorbable plates offer the possibility of reduced stress shielding due to plate degradation causing a progressive reduction in mechanical properties and obviating the need for a second operation to remove the plate.